Exploring work-life balance among professional women in mainland China: A qualitative study - Pan, Ying; Sun, Gong (Frontiers in Psychology, 2022)
This study conducted a qualitative study utilizing semi-structured interviews to explore the barriers and resources of work-life balance of professional women in the context of mainland China. Interviews were selected with full-time employed females who have received higher education and possessed professional qualifications (N=20). The findings reveal the interplay underlying factors in work domain and non-work domain which influence the achievement of work-life balance among Chinese professional women. Participants are found differently in how they perceive and attain their work-life balance due to the personal traits. The findings also highlight additional social support and family support for Chinese professional women in the philosophy of Confucianism. This study contributed to the knowledge on work and life issues through exploring understandings shaping the perceptions and experiences of work-life balance of professional women in mainland China.